The construction of space and audience in contemporary public art practices: three examples from Istanbul - Sönmez, Beril. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2005., 2005)
Temporary art projects taking place outside conventional art institutions like museums and galleries have become common and popular practices in urban areas especially within the last decade. The selection of a public space to make and display "art" opens a new ground to discuss and reconsider contemporary art practices invarious aspects. The main question of the present study is to understand in which extent contemporary public art practices can contribute to overcome the hygienic distinction between the realms of art and everyday life by opening a different level of interactivity where these two separate realms are juxtaposed. This study argues that public art practices can be considered as suggestions about an overall and multi-dimensional transformation in the field of art. Two main axes based on which the transformatory potential of public art practices can be studied are the construction of space and audience. The construction of space, publicity and audience are critical issues in public art practices since different constructions of these concepts in different projects can result in totally diverse practices. Considering that there are multiple manifestations of public art the presentstudy highlights temporary public art projects in which space is conceived in terms of spatial practices of the agents using that space, interaction with the audience is emphasized, people living around or passing-by are considered as creators and participants of the project together with the artists. The whole project, in that sense, refers to a process during which space, artwork and participants are mutually constructing each other. Furthermore, this study points out that public art practices have also the potential to suspend social hierarchies by underlining the possibility of different subject positions for each contributor at least during the project period. Inother words, public art practices are claimed to have the potential to open an alternative platform of changing positions, new sociabilities, interactivity and play. Based on this theoretical framework, specific examples selected from Istanbul are studied in detail in terms of the continuities and discontinuities with museum and gallery practices. With reference to space and audience construction of these three public art projects this study exposes in which dimensions they propose to challenge and transform established definitions of the art world, and to what extent they managed to diverge from conventional art practices and offer new alternatives of making and experiencing art.
Keywords: Public art -- Turkey.; Public spaces -- Turkey.